2010
DOI: 10.1038/ejcn.2009.150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of controlled school-based multi-component model of nutrition and lifestyle interventions on behavior modification, anthropometry and metabolic risk profile of urban Asian Indian adolescents in North India

Abstract: Background/Objectives: To study the effectiveness of a multi-component intervention model of nutrition and lifestyle education on behavior modification, anthropometry and metabolic risk profile of urban Asian-Indian adolescents in North India. Subjects/Methods: Two schools matched for student strength and middle socioeconomic strata were randomly allocated to intervention and control group. Changes in nutrition-related knowledge, attitude, lifestyle practices, food frequency and body image of eleventh-grade st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
198
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(210 citation statements)
references
References 28 publications
9
198
1
2
Order By: Relevance
“…Ser på effekten av automater i forhold til spisevaner Pelsser et al 2009 Behandling av barn med ADHD Ser på forskjeller i selvvurdert helse blant ungdommer Robinson-O'Brien et al 2010 Ingen relevante utfall (laering eller helse), sammenheng mellom å spise det ene og det andre... Rogers et al 2010 Ser på sammenheng mellom kosthold i barndom og sykdom/ikke skolemat, ikke skolesetting Ruottinen et al 2010 Ser på naeringsinnhold og effekten av det Tiltak: Bevisstgjøring og opplaering Singhal et al 2010 Tiltak er bevisstgjøring, ikke mattilbud St-Onge et al 2009 Ser på helseutfall i forhold til omlegging av diett hos barn. Story et al 2006 Vurdering av politikkutforming Suarez-Balcazar et al 2007 Systemendringer i skolen Ser ikke på relevante utfall Wojcicki and Heyman 2006 Vurderer utfall av politikk Omhandler Kina.…”
Section: Studieunclassified
“…Ser på effekten av automater i forhold til spisevaner Pelsser et al 2009 Behandling av barn med ADHD Ser på forskjeller i selvvurdert helse blant ungdommer Robinson-O'Brien et al 2010 Ingen relevante utfall (laering eller helse), sammenheng mellom å spise det ene og det andre... Rogers et al 2010 Ser på sammenheng mellom kosthold i barndom og sykdom/ikke skolemat, ikke skolesetting Ruottinen et al 2010 Ser på naeringsinnhold og effekten av det Tiltak: Bevisstgjøring og opplaering Singhal et al 2010 Tiltak er bevisstgjøring, ikke mattilbud St-Onge et al 2009 Ser på helseutfall i forhold til omlegging av diett hos barn. Story et al 2006 Vurdering av politikkutforming Suarez-Balcazar et al 2007 Systemendringer i skolen Ser ikke på relevante utfall Wojcicki and Heyman 2006 Vurderer utfall av politikk Omhandler Kina.…”
Section: Studieunclassified
“…It was suggested that multi-component interventions (promoting healthy eating, less sedentary behavior and more physical activity), particularly when they target whole communities and environments rather than merely schoolchildren and education, may be more effective in developed countries (17), as well as in developing countries such as in the Pacific (18). In a metropolitan area in North India, a case-control study among school adolescents shows for the first time that a low-cost nutrition and lifestyle educational intervention was effective in improving participants' diet, reducing abdominal adiposity and reducing fasting blood glucose levels, after only a few months (19). Thus, improving the nutritional status of school-age children in developing countries appears feasible, whether undernutrition or overnutrition is the main problem (18,19).…”
Section: The Nutrition-friendly Schools Initiative and Its Rationalementioning
confidence: 99%
“…In a metropolitan area in North India, a case-control study among school adolescents shows for the first time that a low-cost nutrition and lifestyle educational intervention was effective in improving participants' diet, reducing abdominal adiposity and reducing fasting blood glucose levels, after only a few months (19). Thus, improving the nutritional status of school-age children in developing countries appears feasible, whether undernutrition or overnutrition is the main problem (18,19). Furthermore, healthpromoting school approaches, including NFSI, engages parents and other community members and leaders in actively preventing child malnutrition in all its forms, as is claimed for Africa (20).…”
Section: The Nutrition-friendly Schools Initiative and Its Rationalementioning
confidence: 99%
“…Overall, 13 interventions involved school staff, communities, parents, children, and/or families and are referred to as multicomponent interventions in the remainder of this review. Four of the 25 interventions provided an individual counseling component (44)(45)(46)(47).…”
Section: Description Of Included Studiesmentioning
confidence: 99%